Combining electrochemical and quantitative elemental analysis to investigate the sulfur poisoning process of ceria thin film fuel electrodes. Issue 4 (7th January 2022) - Herzig, C.; Frank, J.; Nenning, A.; Gerstl, M.; Bumberger, A.; Fleig, J.; Opitz, A. K.; Limbeck, A.
Abstract : This work deals with the effect of sulfur incorporation into model-type GDC thin films on their in-plane ionic conductivity. Abstract : This work deals with the effect of sulfur incorporation into model-type GDC thin films on their in-plane ionic conductivity. By means of impedance measurements, a strongly deteriorating effect on the grain boundary conductivity was confirmed, which additionally depends on the applied electrochemical polarisation. To quantify the total amount of sulfur incorporated into GDC thin films, online-laser ablation of solids in liquid (online-LASIL) was used as a novel solid sampling strategy. Online-LASIL combines several advantages of conventional sample introduction systems and enables the detection of S as a minor component in a very limited sample system (in the present case 35 μg total sample mass). To reach the requested sensitivity for S detection using an inductively coupled plasma-mass spectrometer (ICP-MS), the reaction cell of the quadrupole instrument was used and the parameters for the mass shift reaction with O2 were optimised. The combination of electrical and quantitative analytical results allows the identification of a potential sulfur incorporation pathway, which very likely proceeds along GDC grain boundaries with oxysulfide formation as the main driver of ion transport degradation. Depending on the applied cathodic bias, the measured amount of sulfur would be equivalent to 1–4 lattice constants of GDC transformed into an oxysulfide phase at the material's grain boundaries.